Analisis Kinerja Ekspor UKM Terhadap Total Ekspor Indonesia pada Masa Presiden Megawati dan SBY - Vita Kartika Sari; Malik Cahyadin (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2009)
The aim of this research is to analyze the potential export activity of Small and Medium Enterprises (SME) in Indonesia, especially in the reign of President Megawati and President Soesilo Bambang Yudoyono. After the monetary crises attacked our economy in 1998, the goverment realized about the important role of Small and Medium Enterprises. This indicates that SMEs are fundamental industry in government point of view both in economic and politic.The methodology applied in this research is Revealed Comparative Adveantage (RCA), descriptive analysis, and SWOT analysis. RCA is used to know how far the comparative advantage of SME’s export. This research uses secondary data. The secondary data were collected through statistic publication from government institutions. SWOT analysis is used for mapping the strategy to creat strong SME’s export activity.Result of this research indicates that the contribution of SME in export activity is still lower than big enterprises. Although, the SME’s RCA showed that some sectors have a comparative advantage to export, but it is not enough to support the national export activity. Keywords: SME, export, Megawati, SBY